Left dislocation and right dislocation in English versus Vietnamese equivalents in some English and Vietnamese short stories from 1990 until now =Cấu trúc dịch chuyển thông tin sang trái và dịch chuyển thông tin sang phải trong tiếng Anh và tương đương tr - Nguyễn, Thị Ngọc Mai (ĐHNN, 2017)
43 p. + CD-ROM + Tóm tắt